Prostimodellens bakgrunn og begrunnelser (Nordic Journal of Practical Theology, 2021)
The article is exploring the background and argumentation for a proposal raised by national bodies within Church of Norway, recommending that the deaneries be the new “hub” for central tasks and responsibilities in the local church: E.g., responsibility for employment, administrative affairs and strategic governance. Leaning on methods developed by Asdal and Reinertsen for analysing public reports and documents, the article surveys the chain of documents promoting such models since the first presentation in 2005. The main arguments rest on the endeavour to establish an organizational unit combining sufficient robustness and competence, closeness to the local parish, and simplification of structures causing resources to be freed up. However, the model seems to carry hidden premises that weaken important aims as, e.g., strategic leadership, involvement and collaboration in the parishes.